STANDARDIZATION OF THE METHOD OF LIBRARY SURFACES OF DETAILS - Husanboyev , Abdulkasim Mamajonovich (Educational Research in Universal Sciences, 2023)
The surfaces of shafts, axles, drums and similar parts exposed to high oxidation and corrosive chemicals in manufacturing plants are subject to rapid corrosion, rapid corrosion under the influence of chemicals, and reduced strength. For this reason, elimination of technological defects and defects that arise during the production process by chemical-thermal treatment of the surfaces of these details and increasing their hardness and corrosion resistance.